The Economics of Investor Protection: ISDS versus National Treatment - Wilhelm Kohler; Frank Stähler (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper scrutinizes the effects of investor-state dispute settlements (ISDS) and national treatment provisions in a two-period model where foreign investment is subject to domestic regulation and a holdup problem. It shows that ISDS can mitigate the holdup problem and increases aggregate welfare, but comes with additional regulatory distortions for the first period. A national treatment provision avoids these regulatory distortions, but implies entry distortions because it makes the holdup problem also apply to domestic firms. If the domestic regulatory framework applies to many domestic firms, a national treatment provision welfare-dominates ISDS.
Keywords: F21; F23; F53; F55; 330; investor-state dispute settlement; national treatment provision; foreign direct investment; TTIP; TPP; regulation